Archaeological herbivore δ13C and δ34S provide a marker for saltmarsh use and new insights into the process of 15N-enrichment in coastal plants. (January 2021) - Guiry, Eric; Noël, Stéphane; Fowler, Jonathan
Abstract: Saltmarshes are tremendously important culturally and ecologically because they can provide abundant nutrient-rich fodder for grazing livestock, with relatively little resource investment. They also perform critical ecological services, including detoxifying water and stabilizing coastlines. For these reasons, methods for investigating the nature and extent of past saltmarsh use have significant potential to provide new insights into patterns in coastal adaptations among past agricultural societies as well as paleoenvironmental change. Stable nitrogen isotope ( δ 15 N) analyses of animal bone collagen have been used to investigate ancient saltmarsh use based on the idea that plants growing in saline and/or coastal regions can have higher δ 15 N values. However, interpretation of δ 15 N evidence for saltmarsh use can be challenging because variation in terrestrial nitrogen sources and cycling can result in similarly elevated in δ 15 N values in animals that did not feed in saltmarshes. Ecological studies show that stable carbon ( δ 13 C) and sulfur ( δ 34 S) isotope analyses are well suited for investigating saltmarsh use because key species (particularly those in the genus Spartina ) that dominate these ecosystems in many areas of the world are C4 plants capable of incorporating sulfuide-derived, 34 S-depleted sulfur. We investigate the utility of δ 13 C, δ 34 S, and δ 15 N for tracking saltmarsh use in archaeological herbivores ( n  = 80) from seventeenth-to-eighteenth-century Acadian settlements in Canada, which were renowned for their agricultural use of saltmarsh ecosystems. Results show extreme variation in δ 13 C and δ 34 S consistent with feeding along C3 -to-C4 and sulfate-to-sulfide-derived sulfur continuums. Significant correlations between δ 13 C and δ 34 S suggests that variation in these isotopic compositions reflects the relative importance of Spartina in past Acadian animal husbandry. These findings indicate that, even in areas where other 13 C-eniched food sources are available (e.g., seaweeds, maize), combined δ 13 C and δ 34 S analyses should be able to identify Spartina use in coastal regions. A strong negative correlation was also found between δ 34 S and δ 15 N, suggesting that processes driving coastal sulfur and nitrogen cycles in the region are coupled (independently of Spartina consumption) and provide new insights into the mechanism behind 15 N enrichment observed in saltmarsh plants. Highlights: Variation in δ 13 C, δ 15 N, and δ 34 S was investigated in 80 archaeological herbivores. δ 13 C and δ 34 S can quantify importance of key saltmarsh plants ( Spartina, spp). Acadian cattle had much greater access to saltmarshes than sheep. Correlation between δ 15 N and δ 34 S shows link between saltmarsh S and N cycles. Higher saltmarsh δ 15 N likely due to coupled nitrification-denitrification in roots.